HUBUNGAN PEKERJAAN DENGAN KEAKTIFAN IBU DATANG KE POSYANDU GELANG DAN KROYO DESA GELANG KULON KECAMATAN SAMPUNG KABUPATEN PONOROGO. - Sumini Sumini; Vera Puspita Anggraini (Akbid Harapan Mulya Ponorogo, 2019)
Activeness is a person's mental and emotional Involvement for achieving goals and taking responsibility in them. Based on the Register of Weighted Weight Cohort Coordinator as an initial problem on November 9, 2016 at integrated health post Gelang and Kroyo on 100 mother toddlers about visit integrated health post, 30 people (30%) were active to integrated health post and 70 (70%) were inactive to integrated health post. A preliminary study of 10 mother-to-toddlers through interviews obtained 3 people (3%) active and 7 people (7%) were inactive. This is because of busyness as Teachers, Nurses, Farmers and Traders. While the mother is active as an IRT. This research is raining to know the relation of mother work with mother activity to come to integrated health post. This type of research is cuantitative with correlational approach and research design with retrospective form. Population in this study were as many as 100 mothers children in integrated health post Gelang and Kroyo, with a sample of 80 mother children by using random sampling tech nique. The study was conducted 12-04-2017. Were one independent variable (work mother of a toddler) and one dependent variable (liveliness of mother come to integrated health post). This research was Book Register Cohort. Data were analyzed using statistical test by using paired Chi- Square Test, level was determined by the value < 0,05. The results of the research showed that most of mother's work are 61 people (76,25%), And Most of under mother children are not as active as 60 people (75%). From the results of calculations performed using Chi-Square Test showed that there is a relationship of work with the liveliness of the mother came to integrated health post in intregated healt post Gelang n Kroyo level with significance level 0,000 < 0,05 and r : 0,695 mean strong relationship. This research was hope midwife to make do counseling about the importance of coming children to integrated health post and increasing the coverage of D/S in Integrated health post Gelang and Kroyo.Midwives are expected to actively to mobilize the people, especially mother toddlers to keep coming to weigh their children.